Implikasi Pemekaran Kabupaten Natuna Terhadap Percepatan Pembangunan Wilayah Kepulauan - Joko Apriadi; Wan Maulidia; Aulia Agustin; Wiky Abial; Bagas Setia Ramadhan (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2024)
This study analyzes the implications of the establishment of Natuna Regency on accelerating development in the archipelagic region. Using a qualitative approach with literature review, the research evaluates the impact of the division on public services, natural resource management, and infrastructure development. The findings indicate that the establishment of Natuna Regency, enacted through Law Number 53 of 1999, has shortened administrative control spans and improved governance effectiveness. Moreover, the acceleration of development in the maritime, energy, and tourism sectors has significantly contributed to local economic growth. However, challenges such as limited human resources and infrastructure in remote areas remain obstacles. This study recommends optimizing local potential and enhancing community participation in development as strategic steps toward equitable development outcomes.